Объяснение:
а) 2HNO3 + CaO = Ca(NO3)2 + H2O
2H(+) + 2NO3(-) + CaO = Ca(2+) + 2NO3(-) + H2O
2H(+) + CaO = Ca(2+) + H2O
б) 2HNO3 + Ca(OH)2 = Ca(NO3)2 +2 H2O
2H(+) + 2NO3(-) + Ca(OH)2 = Ca(2+) + 2NO3(-) + 2H2O
2H(+) + Ca(OH)2 = Ca(2+)+ 2H2O
в) 2HNO3 + CaCO3 = Ca(NO3)2 + CO2 + H2O
2H(+) + 2NO3(-) + CaCO3 = Ca(2+) + 2NO3(-) + CO2 + H2O
2H(+) + CaCO3 = Ca(2+) + CO2 + H2O
Объяснение:
а) 2HNO3 + CaO = Ca(NO3)2 + H2O
2H(+) + 2NO3(-) + CaO = Ca(2+) + 2NO3(-) + H2O
2H(+) + CaO = Ca(2+) + H2O
б) 2HNO3 + Ca(OH)2 = Ca(NO3)2 +2 H2O
2H(+) + 2NO3(-) + Ca(OH)2 = Ca(2+) + 2NO3(-) + 2H2O
2H(+) + Ca(OH)2 = Ca(2+)+ 2H2O
в) 2HNO3 + CaCO3 = Ca(NO3)2 + CO2 + H2O
2H(+) + 2NO3(-) + CaCO3 = Ca(2+) + 2NO3(-) + CO2 + H2O
2H(+) + CaCO3 = Ca(2+) + CO2 + H2O